2020
DOI: 10.3389/fpsyg.2020.578083
|View full text |Cite
|
Sign up to set email alerts
|

When Love Hurts – Mental and Physical Health Among Recently Divorced Danes

Abstract: The last decades of research have consistently found strong associations between divorce and adverse health outcomes among adults. However, limitations of a majority of this research include (a) lack of “real-time” research, i.e., research employing data collected very shortly after juridical divorce where little or no separation periods have been effectuated, (b) research employing thoroughly validated and population-normed measures against which study results can be compared, and (c) research including a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 56 publications
(67 reference statements)
0
24
0
3
Order By: Relevance
“…Berdasarkan analisis dari penelitian-penelitian sebelumnya, diketahui bahwa jenis penelitian yang digunakan adalah kuantitafif dengan mengkorelasikan antara perceraian terhadap kondisi emosi anak usia dini di Panti Asuhan (Kusumawati, 2020),(D'Onofrio & Emery, 2019) dan (O'Hara et al, 2019) mengkorelesaikan antara perceraian dan trauma pada anak usia dini di Panti Asuhan (Srinahyanti, 2018) dan (Sander et al, 2020). Keunggulan dari penelitian-penelitian kuentitatif tersebut adalah mampu untuk mengkorelasikan variabel satu dengan variabel lainnya, akan tetapi tidak mampu untuk mendeskripsikan atau menggali informasi lebih lanjut dan lebih lengkap tentang dampak dari perceraian orang tua terhadap mental emosional anak usia dini, sehingga diperlukan penelitian kualitatif untuk mendapatkan informasi lebih banyak.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Berdasarkan analisis dari penelitian-penelitian sebelumnya, diketahui bahwa jenis penelitian yang digunakan adalah kuantitafif dengan mengkorelasikan antara perceraian terhadap kondisi emosi anak usia dini di Panti Asuhan (Kusumawati, 2020),(D'Onofrio & Emery, 2019) dan (O'Hara et al, 2019) mengkorelesaikan antara perceraian dan trauma pada anak usia dini di Panti Asuhan (Srinahyanti, 2018) dan (Sander et al, 2020). Keunggulan dari penelitian-penelitian kuentitatif tersebut adalah mampu untuk mengkorelasikan variabel satu dengan variabel lainnya, akan tetapi tidak mampu untuk mendeskripsikan atau menggali informasi lebih lanjut dan lebih lengkap tentang dampak dari perceraian orang tua terhadap mental emosional anak usia dini, sehingga diperlukan penelitian kualitatif untuk mendapatkan informasi lebih banyak.…”
Section: Pendahuluanunclassified
“…Hasil eksplorasi yang telah dilakukan kepada anak usia dini korban perceraian sejalan dengan penelitian yang dilakukan oleh Sander et al (2020) yaitu bahwa perceraian membawa dampak bagi anak usia dini yaitu stress dan trauma karena mengingat akan hal yang pernah terjadi pada orang tuanya (Sander et al, 2020).…”
Section: Anak Usia Dini Mengalami Stress Depresi Dan Traumaunclassified
“…Adopting assumptions from stress theory, it can be indicated that this concentration of potential stressors can adversely affect individuals' health and well-being (Pearlin et al, 2005;Pearlin, 2010). Numerous studies have identified the negative effects of dissolution on mental and physical health as well as on psychological well-being and life satisfaction (Hewitt and Turrell, 2011;Hewitt et al, 2012;Sbarra et al, 2014;Sbarra, 2015;Leopold and Kalmijn, 2016;Kalmijn, 2017;Leopold, 2018;Hald et al, 2020;Sander et al, 2020). However, most of these studies had focused only on the dissolution of marriages.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies support the importance of loving relationships, forgiveness, and altruism for health, well-being, and reduced mortality [14][15][16][17][18][19][20][21][22][23][24]. Conversely, deficits in the capacity to love and be loved as evidenced by divorce, conflict, loneliness, and social isolation are risk factors for morbidity and mortality, including depression and anxiety [25,26].…”
Section: Introductionmentioning
confidence: 99%